The Effect of Growth Level, Asset Structure, Liquidity and Profitability on Capital Structure - Wanitasari Wanitasari; Lutvi Alamsyah; Akhmad Mukhlisuddin (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2021)
Competition in the business world encourages financial managers to take decisions carefully, one of which decisions related to capital structure. The purpose of the study is to find out and analyze the effect of growth rates, asset structure, liquidity, and profitability on capital structure in the three banking sector companies incorporated in the Sharia Stock Index Indonesia (ISSI) for the period of 2015 to 2018. The research uses quantitative methods with secondary data obtained from the official bank's website. It uses purposive sampling technique by certain criteria namely BRI Syariah (BRIS), Bank Tabungan Pensiunan Nasional Syariah (BTPS), and Bank Panin Dubai Syariah (BPNS) for the 2015-2018 period. Analysis of the data used in this research is using multiple linear regression analysis with the help of data processing tools IBM SPSS version 20 through the classic assumption test that is normalization test, multicollinearity test, autocorrelation test, and heteroscedasticity test, with hypothesis testing T test, F test and Adjusted R2. It shows that partially the growth rate has no significant effect on capital structure, asset structure has a significant effect on capital structure, liquidity has no significant effect on capital structure, and profitability has a significant negative effect on capital structure. The results of the F test indicate that the growth rate, asset structure, liquidity and profitability have an effect on the capital structure. The amount of Adjusted R2 is 0.857. In the sense that 85.7 percent of the independent variables, while the remaining 14.3 percent of the variables are explained outside the research model.